Implications of Constitutional Court Decisions on The Protection of The Voting Rights of Persons with Mental Disabilities: (Study in Bali Province and Special Region of Yogyakarta) - Syafi'ie, M.; Heryansyah, Despan; Reza, Fatma; Dey, Nabhojit (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2022)
Normatively, the right to vote for persons with mental disabilities in elections was not fully recognized in Article 57 paragraph (3) of Law no. 8 of 2015. This law stipulates that one of the conditions for voters in elections is